Microsurgical Breast Reconstruction in the Obese Patient Using Abdominal Flaps: Complication Profile and Patient Satisfaction. (June 2020) - Boczar, Daniel; Huayllani, Maria T.; Forte, Antonio J.; Rinker, Brian
Abstract : Background: The obesity epidemic has led to larger numbers of obese patients seeking breast reconstruction. The aim of this study was to compare complication rates and patient satisfaction between obese and nonobese women undergoing autologous breast reconstruction using abdominal free flaps. Methods: The records of all patients who underwent microsurgical breast reconstruction by one surgeon for 15 years were reviewed. Patients were divided into obese (body mass index [BMI] ≥ 30 kg/m 2) and nonobese groups. Demographic data, medical and smoking history, cancer type and treatments, surgical details, and complications were recorded. Breast-Q surveys were mailed to all patients, and satisfaction ratings were compared between obese and nonobese patients. Results: There were 109 patients and 149 breast reconstructions, with a mean age of 49 years. Follow-up ranged from 6 to 112 months (median = 19 months). There were 59 patients in the obese group and 52 in the nonobese group. The 2 groups did not differ significantly in median age, follow-up, pathology type, presence of chemotherapy or radiation, or smoking history. Obese group had a higher incidence of mastectomy flap necrosis (19.3% vs 7.7%, P < 0.01) and a higher rate of unplanned reoperations (38.6% vs 21.1%, P < 0.01). Obesity was not associated with a higher risk of microsurgical complications or flap loss (7.0% vs 3.8%, P = 0.21). Overall wound complications did not differ between the groups, but the obese group had a higher rate of severe wound complications requiring operative intervention (15.8% vs 3.8%, P < 0.01). The obese group had a higher incidence of hernia or bulge (10.5% vs 0%, P = 0.03). Thirty-three patients returned completed surveys (response rate of 30%). There was no statistically significant difference in any Breast-Q category associated with BMI. Conclusions: Obesity was associated with higher rates of wound complications, reoperation, and abdominal bulge after microsurgical breast reconstruction. However, patient satisfaction remained high. Patients should be counseled regarding their relative risks, but high BMI should not be considered an absolute contraindication for microsurgical breast reconstruction.